Turkish IBD Organization’s Position Statement on Inflammatory Bowel Disease Management Recommendations During COVID-19 Pandemic - Törüner, Murat; Kalkan, İsmail Hakkı; Akyüz, Filiz; Tezel, Ahmet; Çelik, Aykut Ferhat (Turkish Journal of Gastroenterology, 2021)
The COVID-19 pandemic, caused by the novel severe acute respiratory syndrome coronavirus 2, has resulted in high mortality and morbidityworldwide and is still a growing problem. Inflammatory bowel disease (IBD) is a chronic inflammatory disease for which a substantialnumber of patients are treated with immunosuppressive medications, either occasionally or long-term. Despite the accumulatingevidence, there is still a lack of knowledge about the impact of COVID-19 on IBD patients, especially those who are under immunosuppressivetreatment. Moreover, following the emergence of several COVID vaccines, there are concerns regarding vaccine effectivenessand possible side effects in such patients. In this context, we tried to briefly summarize the accumulating evidence and recommendationsfor the management of IBD in the context of the COVID-19 pandemic.